Pengaruh Penerapan Model Pembelajaran Kooperatif terhadap Hasil Belajar Matematika Siswa ditinjau dari Motivasi Belajar Siswa (Penelitian Eksperimen Penerapan Model Pembelajaran Kooperatif tipe Jigsaw dan STAD) - Dinar, Muhammad; Asdar; Saputri, Sri Anggeliqa (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research aims to know (1) Comparison students’ mathematics learning achievement of high motivated student learning taught by Jigsaw and STAD type of cooperative learning model, (2) Comparison students’ mathematics learning achievement of low motivated students taught by Jigsaw and STAD type of cooperative learning model, (3) there is an interaction between the use of cooperative learning model and student's learning motivation toward student's mathematics learning result. Population in this research was all students on grade X IPA in one of a schoolin Polewali and chosen 2 class by cluster random sampling as sample. Learning design used in this research was factorial design 2x2. Research results showed that (1) Students’ mathematics learning achievement of high motivated student learning taught by Jigsaw type cooperative learning model is higher than students’ mathematics learning achievement taught by STAD type cooperative learning model, (2) Students’ mathematics learning achievement of low motivated students taught by cooperative learning model STAD type is no higher than students’ mathematics learning achievement taught by Jigsaw type cooperative learning model. (3) There is no influence interaction of learning model and student's learning motivation to student's mathematics learning result.